Forming next-generation antibody–nanoparticle conjugates through the oriented installation of non-engineered antibody fragments. Issue 1 (6th November 2017) - Greene, Michelle K.; Richards, Daniel A.; Nogueira, João C. F.; Campbell, Katrina; Smyth, Peter; Fernández, Marcos; Scott, Christopher J.; Chudasama, Vijay
Abstract : Enabling oriented installation of non-engineered antibody fragments on nanoparticle surfaces to create next-generation antibody–nanoparticle conjugates. Abstract : The successful development of targeted nanotherapeutics is contingent upon the conjugation of therapeutic nanoparticles to target-specific ligands, with particular emphasis being placed on antibody-based ligands. Thus, new methods that enable the covalent and precise installation of targeting antibodies to nanoparticle surfaces are greatly desired, especially those which do not rely on costly and time-consuming antibody engineering techniques. Herein we present a novel method for the highly controlled and oriented covalent conjugation of non-engineered antibody F(ab) fragments to PLGA–PEG nanoparticles using disulfide-selective pyridazinedione linkers and strain-promoted alkyne–azide click chemistry. Exemplification of this method with trastuzumab and cetuximab showed significant improvements in both conjugation efficiency and antigen binding capability, when compared to commonly employed strategies for antibody–nanoparticle construction. This new approach paves the way for the development of antibody-targeted nanomedicines with improved paratope availability, reproducibility and uniformity to enhance both biological activity and ease of manufacture.